Gambaran Pola Asuh Orang Tua Dalam Membentuk Karakter Disiplin Anak: Description of Parenting Patterns in Shaping Children's Disciplined Character - Achmad Rifa'i Subagyo; Ramon Ananda Paryontri (Universitas Muhammadiyah Sidoarjo, 2025)
This study discusses the role of parenting patterns in shaping children's discipline character within the family context. General Background: Character education has become a central issue in contemporary educational discourse, particularly regarding the formation of discipline in children from an early age. Specific Background: The family environment, especially parenting patterns, plays a fundamental role in guiding children’s behavioral development and moral internalization. Knowledge Gap: Previous studies have widely addressed character education; however, limited attention has been given to a focused examination of how specific parenting approaches relate to discipline character formation within the family setting. Aims: This research aims to analyze the relationship between parenting patterns and the development of discipline character in children. Results: The findings indicate that parenting patterns are closely associated with the establishment of disciplined behavior, where consistent guidance, supervision, and value internalization contribute to structured behavioral development. Novelty: This study highlights a contextual analysis of parenting practices as a structured foundation for discipline character formation in the family sphere. Implications: The results provide practical recommendations for parents and educators to strengthen discipline character through intentional and consistent parenting strategies. Keywords: Parenting Patterns, Discipline Character, Character Education, Family Environment, Child Development Key Findings Highlights: Parenting approaches are directly related to structured behavioral development in children. Consistent guidance and supervision support moral internalization processes. Family-based character formation provides a foundational framework for early behavioral regulation.